Efficacy of a novel inhibitor of vascular adhesion protein-1 in reducing albuminuria in patients with diabetic kidney disease (ALBUM): a randomised, placebo-controlled, phase 2 trial. Issue 12 (December 2018) - de Zeeuw, Dick; Renfurm, Ronny W; Bakris, George; Rossing, Peter; Perkovic, Vlado; Hou, Fan Fan; Nangaku, Masaomi; Sharma, Kumar; Heerspink, Hiddo J L; Garcia-Hernandez, Alberto; Larsson, Tobias E
Summary: Background: Many patients with diabetic kidney disease have residual albuminuria and are at risk of disease progression. The ALBUM trial investigated the efficacy of a novel, orally active inhibitor of vascular adhesion protein-1, ASP8232, compared with placebo for reducing albuminuria in individuals with type 2 diabetes and chronic kidney disease. Methods: In this randomised, double-blind, placebo-controlled phase 2 trial, we randomly assigned individuals (aged 18–85 years) from 64 clinical sites in nine European countries to receive ASP8232 40 mg or placebo orally once daily for 12 weeks using a web-based randomisation schedule (block size 4), stratified by country. Eligible patients had a urinary albumin-to-creatinine ratio (UACR) of 200–3000 mg/g, an estimated glomerular filtration rate of at least 25 mL/min per 1·73 m 2 but lower than 75 mL/min per 1·73 m 2, HbA1c less than 11·0% (97 mmol/mol), and stable treatment with angiotensin-converting enzyme inhibitors or angiotensin receptor blockers and antidiabetic medication for 3 months or more. The primary endpoint was mean change from baseline to week 12 in log-transformed first morning void UACR, which was assessed in all patients who received at least one dose of study drug and had at least one post-baseline UACR measurement (full analysis set). Safety was assessed in all patients who received at least one dose of study drug. Participants and investigators were masked to treatment allocation. This trial is registered withClinicalTrials.gov, numberNCT02358096 . Findings: 125 participants were randomly assigned to receive ASP8232 (n=64) or placebo (n=61), of whom 120 (60 in each group) were included in the full analysis set; all participants were assessed for safety endpoints. At 12 weeks, UACR decreased by 17·7% (95% CI 5·0 to 28·6) in the ASP8232 group and increased by 2·3% (−11·4 to 18·1) in the placebo group; the placebo-adjusted difference between groups was −19·5% (95% CI −34·0 to −1·8; p=0·033). 39 (61%) patients in the ASP8232 group and 34 (56%) patients in the placebo group had a treatment-emergent adverse event, of which 16 in the ASP8232 group and four in the placebo group were drug-related. The most frequently reported adverse events that were possibly drug-related in the ASP8232 group were renal impairment (five patients) and decreased eGFR (three patients); in the placebo group, no single drug-related treatment-emergent adverse event was reported by more than one participant. Interpretation: ASP8232 is effective in reducing albuminuria in patients with diabetic kidney disease and is safe and well tolerated. These findings warrant further research to ascertain the effect of ASP8232 on delaying progression of diabetic kidney disease. Funding: Astellas.